The Challenge of Migration in a Janus-Faced Europe - Zanfrini, Laura; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
'Laura Zanfrini's persuasively-argued work provides a succinct discussion on the politics of immigration and the legacies of the guestworker model with original analysis that highlights the paradoxes of immigration governance.' -Erica Consterdine, Sussex Centre for Migration Research, University of Sussex, UK This book critically investigates the origins and consequences of the Janus-faced character of attitudes and policies towards migrants that seek to penetrate "Fortress Europe". Beginning with an examination of its founding ambitions, it locates the roots of an ingrained ambivalence in the legacies of the post-war period and the unresolved tension between the economicism of the European approach to labour migration and the philosophy of rights and solidarity embedded in the EU project. It highlights how the formalization of citizenship rights has produced both formal pathways towards inclusion for migrants and, in their selective eligibility criteria, exclusive systems of civic stratification. The author links this oscillation between positions of closure and openness to the paradoxical trade-offs in migration policies, in particular labour market integration, demonstrated through unequal labour market outcomes, lower social mobility and educational attainments. The issues faced by migrants' offspring in Europe are examined as paradigmatic of the struggle to balance competing calls for both pluralism and uniformity: to create a diverse society that can also project a homogenous collective identity. This balanced overview will provide an invaluable resource for students of migration studies, European politics, public policy, international relations and the sociology of racism.
Chapter 1: Introduction. The Unexpected Legacy of the post-WWII Migratory Regime -- Chapter 2:The (Un)Ethical Foundations of the Borders of Membership. Inclusion versus Exclusion -- Chapter 3: The "Schizophrenia" of the European Approach. Equality versus Discrimination -- Chapter 4: The Identity Challenge. Diversity versus Uniformity -- Chapter 5: The (Un)Ethical Boundaries of the European Fortress. Openness versus Closure -- Chapter 6: Conclusions. The refugee crisis: A Prophetic Challenge for European Societies.
Keywords: Emigration and immigration; Europe -- Politics and government; Social structure; Equality; Political planning; Race; Human Migration; European Politics; Social Structure; Public Policy; Race and Ethnicity Studies